Book Reviews (The Australian journal of anthropology, 2002)
Book reviewed in this article: Francoise Dussart. The Politics of Ritual in an Aboriginal Settlement: Kinship, Gender, and the Currency of Knowledge. Han-Dieter Evers and Rudiger Korff. Southeast Asian Urbanism: The Meaning and Power of Social Space. Susan Greenwood. Magic, Witchcraft and the Otherworld: An Anthropology. IWGIA. The Indigenous World 1999–2000. Christian Emi (ed.) A. Margaret McArthur. The Curbing of Anarchy in Kunimaipa Society. Edited by Douglas Oliver John McCreery. Japanese Consumer Behaviour: From Worker Bees to Wary Shoppers. Diane M. Nelson. A Finger In The Wound: Body Politics in Quincentennial Guatemala. Lidia D. Sciama and Joanne B. Eicher (eds). Beads and Bead Makers: Gender, Material Culture and Meaning. John W. Traphagan. Taming Oblivion: Aging Bodies and the Fear of Senility in Japan.